Dramatyczność w antycznej teorii narracji i wybranych gatunkach narracyjnych epoki cesarstwa - Bartol, Krystyna (Przestrzenie Teorii, 2008)
The concept of dramaticality, re-emerged after Aristotle as a topic of rhetorical interest in the classification of narrative which extends beyond the forensic. The essential point of the Hellenistic grammarians' tripartite division of narrative was the category which comprises 'made-up events which nevertheless could have happened'. In Greek this category is often called plasma ("invention") or dramatikon. It seems to suggest that this type of narrative was a literarily elaborated and emotionally charged account of actions and characters invented by the writers, and approximated to our idea of fiction. Dramatically oriented presentation of plots was useful first of all to novelists of the Imperial period. The stress on producing a narrative sustained dramatical pattering and imagery, is also to be found in the epistolary and biographical genres of this time.